Literatura de autoria feminina: constituição do sujeito mulher em "Marias", de Janaína Azevedo - Reis, Elaine da Silva (2018)
This Theory systematizes an inquiry turned to the investigation of the constitution of the subject woman in the stories of "Marias" (1999), of Janaína Azevedo. Understanding the literature as space of constant event and updating of the speeches, we believe that the literary texts also have to when historical-partner was read like a product and ideologically what comes true with the history and with the memory. For so much, we take like base the theoretical presuppositions of the Discourse Analysis (AD) of French line, with base mainly in the studies of Foucault (2004), Pêcheux (1997), Courtine (2006) and Robin (1977), from which the texts are conceived like propaying fountains of speeches, having in mind that representations materialize partner - historical and cultural what mark the identity of the subjects. We focus, in special way, the ideas foucaultianas, in what it concerns the concepts of “real Wills” and “Relations of power” and we turn to the discussion on feminine authorship, from authors like Perrot (2013), Soihet (2013), Badinter (2005), Telles (1992) and Woof (1985). To understand the questions relative to the constructions identitárias, we resort to the Cultural Studies, through Hall (2006), Bauman (2005) and Silva (2000). As for the methodology, it is the question of a qualitative inquiry of documentary hallmark, which corpus is composed by six of thirteen stories that compose the selected work, namely: "Women of the gang", "Rituals", Carpentry "," Give me your hand, O virgin "," Comungado Banquete " and " Aunt Dona ". The objectives norteadores are the next ones: to investigate the speeches that constitute the subject woman in “Marias“; to analyse like the "voice" of feminine authorship woman builds the representations of the subject in the stories of “Marias“; to identify the real wills, the relations of power and, consequently, the places granted to the woman in the above-mentioned stories, as well as it will identify the stereotypes that constitute the identity of the subject woman. After the analysis of the stories, before the data, was possible to realize that the constitution of the subject woman in “Marias“ happens from speeches that mark the identity of the woman, through multifaceted representations of the woman in the contemporaneousness and for the resignification of the biblical / religious speech. In the opaqueness of the writing of Janaína Azevedo, we observe a shock of identities provoked in the confrontation of the religious speech, which permeates all the analysed stories, and the feminist speech that looks to fight the fetters that the woman subjects to a man in centuries. We see in the work of the above-mentioned author moments of submission versus moments of resistance, through the represented women. Janaína Azevedo goes between the sky (holy) and the hell (profane), outlining different ways of being a woman in the land.